(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
A significant role in eliminating and reducing the degree of negative impacts on the city belongs to plants that perform not only a decorative, aesthetic, but also a protective and hygienic function. Woody plants purify, moisten and enrich the atmosphere of cities with oxygen, change the radiation and temperature regimes, and reduce the strength of wind and noise. Being under constant stress, plants turn on the adaptive mechanisms of biochemical, physiological, and morphological rearrangements. The article analyzes the problems of landscaping the city of Chirchik. The problems of the old fund of urban gardening are revealed. Presented are the modern most promising methods of planting greenery in the city